República e contemporaneidade: em busca do Ethos Republicano-Democrático - Santos, Marcos Antonio Gonçalves dos (Universidade Federal de São Carlos, 2025)
The field of education seems to have given preference to the debate concerning democracy over that which refers to issues of the republic. Many works have been devoted to explaining and promoting a certain democratic ethos within the school context; however, it seems to us that there has been a certain neglect of what would constitute the republican ethos. The latter is centered on the common good—that is, the idea of what is public and of collective interest—understood as the very essence of politics. Through a genealogical inspiration, we seek to demonstrate that the rise of the animal laborans and the implementation of the new neoliberal art of government (biopolitics/governmentality) have dissolved or gravely corrupted the ideal represented by the Republic. Neoliberal rationality, through its governmentality, has been the major obstacle preventing the field of education from teaching and promoting what we could call the republican-democratic ethos. Therefore, we defend the thesis of the need to create what we refer to as a Republican-Democratic Ethos.
Republic and Contemporaneity: in search of the Republican-Democratic Ethos
Keywords: República; Educação; Animal Laborans; Neoliberalismo; Biopolítica; Ethos Republicano-democrático; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; 4. Educação de Qualidade